Pengaruh Job Boreout dan Kebahagiaan di Tempat Kerja Terhadap Counterproductive Work Behavior Pada Pegawai di Kantor Wali Nagari Kecamatan Simpang Alahan Mati dan Bonjol dengan Gender Sebagai Variabel Moderasi - Soviya, Fenti; Rino, Rino (Jurnal Salingka Nagari, 2024)
The aim of this research is to find out the influence of job boredom and happiness at work on CWB among Wali Nagari office employees in Simpang Alahan Mati and Bonjol sub-districts with gender as a moderating variable. The population used was all employees at the Wali Nagari office in the Simpang Alahan Mati and Bonjol sub-districts and the sampling technique used saturated samples. The data used is primary and secondary data with data collection techniques through distributing questionnaires and processed using SmartPLS. The results of this research are that job boreout has a significant effect on CWBI and CWBO. Happiness at work has a significant effect on CWBI and CWBO. Gender cannot moderate the effect of job boreout on CWBI employees at the Wali Nagari office in Simpati and Bonjol sub-districts. Gender moderates the influence of job boreout on CWBO of Wali Nagari office employees in Simpati and Bonjol sub-districts. Gender cannot moderate the influence of happiness at work on CWBI employees at the Wali Nagari office in Simpati and Bonjol sub-districts. Gender moderates the influence of happiness at work on the CWBO of Wali Nagari office employees in Simpati and Bonjol subdistricts.